(3CfhGQ GdabGgIs - (3GdLfGMj, GdfLaj, cGTa GdZWGA, MSf Hf LYaQ Hf NVQ, J (B1262 (3g`s
(3ChdgG (B:s
(3cJGH GdQgf GdQgf dZI GdKHGJ hGdOhGe hGdMHS, hYdjg bhd JYGdi (B{ (3cd faS HeG cSHJ QgjfI (B} ...s
(3BNQgG (B:s
(3hgd Jbhe ebGegG GdLYGdI HfGA Ydi GZJaGQ GdLgGdI ajgG hGZJaGQ YOe GdJMbb hLgGf CjVG hGdefY Chdi hCXgQ(B. (3Je cJGH GdeRGQYI hGdeSGbGI(B...(3hjJdhg cJGH Gdhbas
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B:(3L(B1(3,U(B534s
(3GdPQjYI(B:(3L(B2(3,U(B244(3,Qbe (B1702s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis